Relaties, seksualiteit en gezin: Een zaak van publiek én theologisch belang - Dillen, Annemie (Tijdschrift voor theologie, 2015)
Ecclesiastical and theological pronouncements on subjects like family, relationships and sexuality are currently attracting extra attention in the light of the two synods on the family. This article argues that theological and ecclesiastical pronouncements on family, relationships and sexuality are indeed meaningful and even necessary. First, it points out the many societal influences that families are exposed to; ecclesiastical and theological pronouncements could help people determine their position. Next, ecclesiastical and theological pronouncements are linked to the societal importance of healthy relationship within the family. The second part of this essay argues from a theological point of view that speaking about God always presupposes that attention is paid to the everyday experiences in the family, relationships and sexuality. The third part develops building blocks for such a theology and focusses on a spirituality that centers on trust and letting-go, combined with a theology of ‘recognition’. It holds that the attention should mainly be directed towards the positive rather than the shortcomings.